The Unity of Luke—Acts in Recent Discussion - Bird, Michael (Journal for the study of the New Testament, 2007)
This article surveys the debate about the unity of Luke—Acts in recent scholarship. The study concentrates on monographs and articles written after Mikael C. Parsons and Richard I. Pervo's volume Rethinking the Unity of Luke and Acts, and identifies the recent contribution that reception-history studies have brought to the debate. This is followed with a brief analysis of the flashpoints in the debate, and a discussion of what is at stake for Lukan studies.